Foundations of chemistry in the laboratory / Morris Hein ... [et al.] - Hein, Morris (J. Wiley & Sons, 2007)
Learning the fundamentals of chemistry can be a difficult task to undertake. The market leader for 35 years, Foundations of College Chemistry has helped countless readers master the chemistry skills they need to succeed. The book is known for its accuracy and direct writing style.